Learning Management in Islamic Educational Institutions - Abdan, Syarwani; Sugiarti, Erna; Sari, Tanti Nurmala; Siminto; Najah, Triwid Syafarotun (Jurnal Manajemen Pendidikan, 2024)
Background The diversity of types of Islamic educational institutions makes learning management a very important role, namely as a center in ensuring that the education provided is not only relevant to religious values, but also in accordance with the development of science and technology. Purpose The purpose of writing this journal is to describe and explain learning management in Islamic Educational Institutions. Design/method/approach The research method used is a literature review which involves collecting literature from various sources such as books, journal articles, and relevant dissertations. The literature that has been collected is then evaluated for quality and relevance through critical analysis of abstracts, research methods, and main findings. Results The results of the educational study indicate that learning management in Islamic institutions as a whole is able to create a teaching and learning atmosphere by applying academic aspects of Islamic values, learning management is a structured planning process to achieve effective and efficient educational goals in accordance with Islamic principles. Contribution/value The development of religious culture in Islamic educational institutions through extracurricular activities not only enriches academic learning, but also strengthens the moral and spiritual foundations of students which are important in forming a generation with noble character.